Pengaruh Initial Public Offering (IPO) Terhadap Rasio Keuangan Perusahaan Yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2016-2021 - Putri, Neng Salma Amelia; Susilawati (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to examine and analyze the impact of the Initial Public Offering (IPO) on the financial ratios of companies listed on the Indonesia Stock Exchange (IDX) within the 2016-2021 timeframe. The analysis is conducted using three main variables as financial ratio benchmarks: profitability ratio, liquidity ratio, and solvency ratio. A quantitative approach was applied to this study using the Wilcoxon Signed-Rank Test non-parametric difference test method and the Multivariate Analysis of Variance (MANOVA) test to analyze the PRE-IPO and POST-IPO company financial statements. The results of the analysis using the Wilcoxon Signed-Rank Test indicate that the Initial Public Offering (IPO) has a significant effect on the profitability ratio and solvency ratio, but has an insignificant effect on the liquidity ratio. Meanwhile, the results of the MANOVA test simultaneously indicate that Initial Public Offering (IPO) has an insignificant effect on all financial ratios analyzed. This study provides insight into how the company's financial ratios change due to the Initial Public Offering (IPO) and has the potential to become a reference for investors and company management for the strategic decision-making process.